Introducing The City’s Cultural Heritage to The Students of Elementary School Through Picture Story Book - Hariyanti, Rosana; Nurhayani , Ika; Rahmadhani , Kurnia; Asyifa, Nadhifa Luqyana Wati Cahya; Ramadhany , Nabila Shifa; Zahra, Aurell Denastha; Prameswari, Auryn Zahra Choirunnisa (Jurnal Gramaswara: Jurnal Pengabdian kepada Masyarakat, 2024)
This community service activity aims to introduce elementary school students to the cultural heritage of their city. The focus was on Kampung Kayutangan Heritage, a historically significant area located in the heart of Malang City. The approach involved writing and publishing a picture storybook about the Kayutangan Heritage, which was subsequently donated to Brawijaya Smart School (BSS). Following the donation, a storytelling session was conducted for the students. This initiative not only enhanced students' awareness of the cultural and historical significance of their local heritage but also fostered a sense of responsibility toward its preservation.